Internalization of Islamic Boarding School Values in an Indonesian Islamic Educational Institution - Sri Haryanto (AL-ISHLAH: Jurnal Pendidikan, 2022)
The education system and culture attached to Islamic boarding schools are one of the historical facts that play a role in building and guarding the Indonesian nation. This study aims to determine the development of Islamic educational institutions (PTAI) in the era of globalization and to determine the application of PTAI in Indonesia. This research uses a descriptive qualitative method which is carried out using a case study and the object of this research is an Islamic university, Central Java. The result reveals that Islamic boarding schools in the education system occupy an important position. Ethical Politics causes the transformation of science to run rapidly. Islamic boarding school-based PTAI, has a strong base. Its scientific paradigm is normative as well as historical, theoretical and practical, immanent and transcendent. The values internalized by the institutions are adapted from several boarding schools. Those values are Al-Amanah, Al-Tawadlu', Al-Istiqamah, Al-Uswah, al-Hasanah, Al-Tawashshuth, At-tawâzun, Al-Barakah and Tawasul ilmi.